Impact of Serum Folate and Vitamin B12 on Mental Health in Patient Admitted at Razi Psychiatric Hospital - Aml Koubas; Yasmein Alshibani; Huria Dardar; Rajaa Alshwesh; Zinab Elfituri (AlQalam Journal of Medical and Applied Sciences, 2024)
Vitamin B12 (cobalamin) is one of the essential vitamins that affect various systems in the body, including the central nervous system and plays an important role in the metabolism of the nervous system, although its exact role under pathological conditions is not fully understood. The present study aimed to assessing vitamin B12 & serum folate in patient admitted at Razi psychiatric hospital. A cross section study subjects were inpatients with psychiatric disorder, patients from 21 to 60 years old. In this group of 40 psychiatric patients, there is no evidence of clinically relevant changes in serum vitamin B12 and folate level. Vitamin B12 deficiency can occur despite “normal” serum cobalamin levels; therefore, measuring homocysteine and methyl malonic acid can decrease false-negative findings. فيتامين ب12 (الكوبالامين) هو أحد الفيتامينات الأساسية التي تؤثر على أنظمة مختلفة في الجسم، بما في ذلك الجهاز العصبي المركزي و تهدف الدراسة الحالية إلى تقييم فيتامين ب12 وحمض الفوليك في المصل لدى المرضى الذين تم دخولهم لمستشفى الرازي للأمراض النفسية. كانت الدراسه على مرضى داخليين يعانون من اضطرابات نفسيه تتراوح أعمارهم بين21 إلى 60 عامًا. في هذه المجموعة من 40 مريضًا نفسيًا، لا توجد أدلة على تغييرات سريرية ذات صلة بمستوى فيتامين ب12 وحمض الفوليك في المصل. يمكن أن يحدث نقص في فيتامين ب12 بالرغم من أن مستويات الكوبالامين في المصل طبيعية؛ لذلك، يمكن أن يؤدي قياس الهوموسيستئين وحمض الميثيل مالونيك إلى تقليل النتائج السلبية الكاذبه